2021
DOI: 10.2105/ajph.2020.306063
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the COVID-19 Misinfodemic With Network Interventions: Network Solutions for Network Problems

Abstract: Amid the COVID-19 global pandemic, a highly troublesome influx of viral misinformation threatens to exacerbate the crisis through its deleterious effects on public health outcomes and health behavior decisions. This “misinfodemic” has ignited a surge of ongoing research aimed at characterizing its content, identifying its sources, and documenting its effects. Noticeably absent as of yet is a cogent strategy to disrupt misinformation. We start with the premise that the diffusion and persistence of COVID-19 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The most frequent are the artic early access (5678) followed by proceedings papers (1211), editorial mater reviews (360). Other document types were letter (223), book review (177), me (106) and news items (46). The remaining documents are present in a very s The majority of the papers (8299) are written in English.…”
Section: Document Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequent are the artic early access (5678) followed by proceedings papers (1211), editorial mater reviews (360). Other document types were letter (223), book review (177), me (106) and news items (46). The remaining documents are present in a very s The majority of the papers (8299) are written in English.…”
Section: Document Typesmentioning
confidence: 99%
“…So far, research [30,31,77] has shown that false or misleading discourse regarding health information comes in various forms that require different reactions. New topics of interest are those related to mental and psychosocial health during and after the pandemic [105] or the way in which online platforms and social networks will handle these threats [106]. A solution may come from infodemiology that aims to study how best to manage these threats [16,107].…”
Section: Conceptual Structure Of Knowledge Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Carpal tunnel syndrome (CTS) may be a nonspecific manifestation of hereditary ATTR amyloidosis (ATTRm). Amyloid deposits in the transverse carpal ligament have also been observed in recurrent CTS [ 13 , 14 , 15 ]. Anatomic innovation variants such as the median-ulnar junction (MUC) branch, also known as the Martin-Gruber anastomosis, can lead to interpretation errors in nerve conduction studies of patients with carpal tunnel syndrome [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The following are available online at , Figure S1: Normalized number of ‘active’ comments available on the Interia Web page related to vaccination, assuming the lifetime of the comment to be 4, 8 or 16 weeks, Figure S2: Periodogram of the Interia data, using frequencies derived from weekly time stamps, Figure S3: Top panel: distribution of the ratio of posts identified by the keyword search to the overall thread size as function of the thread size for the topmost threads within the six main subreddits, Figure S4: Graphical interface of the NetLogo simulation program, with main components marked, Figure S5: Examples of typical time evolution of the number of patients with opinion below the vaccination threshold (antivaxxers), Figure S6: Examples of typical time evolution of the number of active messages in the system, Figure S7: Periodograms of the simulated number of active messages, using the abstract simulation fre-quencies scaled by a factor of 4.5, Table S1: Parameters used in simulations. References [ 88 , 89 , 90 , 91 , 92 , 93 , 94 ] are cited to in Supplementary Materials .…”
mentioning
confidence: 99%